Traffic medicine and road safety in Germany - Klaus Püschel (194251) (2015)
In place of Germany as a whole, the situation of traffic medicine in Hamburg is described. As a metropolis in the north of Europe and hub for the land traffic, maritime transport and air traffic – Hamburg is a good location for the topic of traffic safety. In particular the maritime medicine as well as the production of traffic airplanes define our city. Furthermore Hamburg and the University Medical Center of Hamburg-Eppendorf (UKE), as a science location, have made a name for itself especially in the area of forensic medicine. The legal medicine and traffic medicine are key aspects in research and teaching of the UKE. The traffic medicine/road safety under the perspective of forensic medicine focuses on the following main-areas: •Determination and prognosis of fitness to drive with respect to age, illness and substance abuse/dependence •Driving under the influence of alcohol, drugs and medicaments. •Chemical-toxicological analyses, methodology, accreditation of laboratories, drug recognition training, breath alcohol analyses •Demographic change, drivers licence and old age medical condition •Accident reconstruction, with special respect to the investigation of drivers (dead or alive) Germanwings Flight 9525 (4U9525/GWI18G) is a central point of discussion. It was a scheduled international passenger flight from Barcelona in Spain to Düsseldorf Airport in Germany. On 24 March 2015, the aircraft, an Airbus A320-200, crashed in the French Alps. All 144 passengers and six crew members were killed; this was deliberately planned by the co-pilot. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.93